Mapping China’s triple interlinkage: a quantile connectedness analysis of agricultural, energy, and policy shocks - Song, Yun; Wang, Kai-Hua; Liu, Hong-Wen; Moldovan, Nicoleta-Claudia (Frontiers in Sustainable Food Systems, 2025)
This study investigates spillovers among agricultural commodity future price (AFP), crude oil price (COP), and economic policy uncertainty (EPU) from China perspective, using quantile connectedness method. The empirical findings indicate that AFP, COP, and EPU exhibit significantly elevated volatility connectedness at extreme quantiles compared to median levels, revealing intensified cross-market contagion during economic uncertainty and tail events. Moreover, the dynamic characteristics of AFP, COP, and EPU are empirically validated, while historical crises are shown to amplify these spillover mechanisms substantially. The key innovation lies in integrating EPU within the COP-AFP analytical paradigm, where dynamic quantile shifts capture their interdependencies across market conditions, thereby expanding the theoretical scope. Thus, this research further provides policies, such as agricultural market monitoring mechanism and international economic cooperation, for multiple market participants.